Community Response to Mining Business: Case Study on Romang Island Southwest Maluku Regency - Godlief Johansz; August E Pattiselanno; Yolanda MTN Apituley; Junianita Fridianova Sopamena (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Mining businesses can have a positive or negative impact on the surrounding community. This study aims to analyze the community's response to the mining business on Romang Island, Southwest Maluku Regency. The population in this study is the Romang Island community which is mapped out against and supports spread over the three villages, namely, Solath, Jerusu, and Hila with a total sample of 52 people. The results of the study indicate that there are public expectations of the company to pay attention to their welfare through various efforts, including: paying attention to the representation of the community working in the company, paying attention to the process of community empowerment, paying attention to educational and health facilities and infrastructure, as well as paying attention to the existence of the environment so that it does not harm the community. The behavior of the farming community towards PT. Gemala Borneo Utama (GBU) 86.54% strongly supports the company's presence, supported by the perception of respondents 53.85 percent indicating the availability of jobs, 23.07 percent indicating an increase in people's income, 9.62 percent stating an increase in accessibility.